On quasi-periodicity properties of fractional integrals and fractional derivatives of periodic functions. Issue 1 (2nd January 2016) - Area, I.; Losada, J.; Nieto, J.J.
ABSTRACT: This paper is devoted to the study of quasi-periodic properties of fractional order integrals and derivatives of periodic functions. Considering Riemann–Liouville and Caputo definitions, we discuss when the fractional derivative and when the fractional integral of a certain class of periodic functions satisfies particular properties. We study concepts close to the well known idea of periodic function, such as S-asymptotically periodic, asymptotically periodic or almost periodic function. Boundedness of fractional derivative and fractional integral of a periodic function is also studied.